PITUTUR LUHUR UNTUK PEMBERANTASAN KORUPSI DI INDONESIA DALAM PERSPEKTIF KEBIJAKAN HUKUM PIDANA - Moch. Choirul Rizal; M. Lutfi Rizal Farid (Universitas Kristen Satya Wacana, 2017)
The study of this idea has a focus on “pitutur luhur” for eradicating corruption in Indonesia. The writing of this idea uses a penal policy approach. It is found that the eradication of corruption has not found significant success. One indicator is the Indonesian Corruption Perceptions Index that has not improved. Apparently, the excessive action taken by the KPK does not reduce the level of corruption much. In this regard, an action plan which is presumed to be worth